Entertainment : screen, stage & stars - Morley, Jacqueline (New York : F. Watts, 1994)
Traces the history of such forms of entertainment as drama, dance, opera, and film.
Popular traditions -- Religious drama -- Indoor theater -- Ballet -- Music hall and panto -- The talkies -- Entertainment today.
Includes index.
Wilson's Junior High School.
7.4
4-6
5-8
Keywords: Performing arts -- History -- Juvenile literature; Theater -- History -- Juvenile literature; Performing arts -- History; Theater -- History; Performing arts -- History; Theater -- History